The Analysis Of Figurative Language In Novel Looking For Alaska - Kasimo, Meldiana Kewa Sari; Ayu Made Puspani, Ida (Peneliti.net, 2026)
This study aims to analyse the use of figurative language in John Green's novel Looking for Alaska. This study uses a qualitative method with a descriptive approach to identify and classify types of figurative language based on Larson's theory (1998), namely metonymy, synecdoche, idioms, euphemisms, hyperbole, metaphors, and similes. The results of this study indicate that this novel is rich in figurative language, which strengthens characterization, deepens emotions, and enriches the story's meaning. Each type of figurative language plays a distinct role in creating atmosphere, conveying messages, and enhancing the reader's experience. These findings underscore the importance of figurative language in literary works, particularly in building narrative depth and appeal. This study is expected to enhance appreciation for the beauty of figurative language in literature and serve as a reference for further research on linguistic style in literary works.